Pelaksanaan Webinar Dengan Tema Implementasi Digital Marketing Dalam Menarik Minat Konsumen di Era Pandemi COVID-19 Khususnya di Desa Ketapang - Dasmawan, Deris; Afandi, Kevin; Puspitasari, Nusyifa Tassya; Anggrelia, Septy; Damayanti, Krisna; Ningrum, Jeni Astuti; Rahmaniasan, Viera; Nurholifah (Lembaga Penelitian dan Pengembangan Teknologi dan Rekayasa, Yayasan Ahmar Cendekia Indonesia, 2021)
The purpose and objective of holding a training webinar with the theme of implementing digital marketing in attracting consumer interest in the era of the covid-19 pandemic in community service activities in the Ketapang village is to help people who have difficulties in doing marketing for their products in the era of the covid-19 pandemic where they can use social media by using attractive designs to attract consumers. Government policies such as PPKM during the pandemic often make business owners worry about their business. They are afraid that their business will not go well, because it is important to use social media to market their products to attract consumers, even if not directly.